Teachers' Time Use and Affect Before and After COVID-19 School Closures. (January 2022) - Jones, Nathan D.; Camburn, Eric M.; Kelcey, Benjamin; Quintero, Esther
Several large-scale survey efforts have attempted to understand teachers' experiences in the early months of the pandemic. Our study complements this literature by providing direct evidence of teachers' work prior to and after the onset of COVID-19. We leverage unique longitudinal time use and affect data on 131 teachers from one district across the 2019–2020 school year. Specifically, we provide a full accounting of teachers' instructional activities, their reports of their positive affect and negative affect while engaged in these activities, and the extent to which teachers' work experiences changed post-COVID. Our results suggest a large reduction in teachers' daily instructional minutes, which were replaced with increased planning, paperwork, and interactions with colleagues and parents. Teachers' overall positive and negative affect did not change post-COVID. But teachers' affective responses to specific work activities did. Post-COVID, we saw increases in teachers' positive affect when with students.